A Distance Compensated Approach Used in Wireless Passive Pressure Sensor Readout System for High Temperature Application. (16th November 2015) - Hong, Yingping; Liang, Ting; Zheng, Tingli; Cao, Qun; Zhang, Wendong; Liu, Wenyi; Zhang, Huixin; Xiong, Jijun
Abstract : This paper proposed a distance compensated measurement system for a wireless passive sensor based on the high temperature cofired ceramics (HTCC) applied to high temperature environment. The sensor model is provided and fabricated. Also, a telemetric measurement system consists of a readout instrumentation and a heat insulation unit is described due to the thickness of heat insulation material between the sensor and readout unit's inductance coils in high temperature testing environment. Consideration of the leakage inductance and parasitic parameters which depend on the coupling distance is equivalent to the thickness of heat insulation material, and a distance compensated method is presented. The compensation is based on the mathematical feature of the testing results from readout unit which show us information about the relation between the extracted resonant frequencies. This method can be used simply and reliably in the other telemetric mutual inductance coupling readout system as a viable solution to compensate the coupling distance related error when inductive coupling is varied. It has been experimentally tested, and the results are in good agreement with those measured by a reference impedance analysis instrument. Theoretical explanations, experimental results, and discussion are reported.